2022
DOI: 10.7759/cureus.27552
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Emergency General Surgery Operations in the Setting of COVID-19 and Impact of Strategy of Non-Operative Management on Outcomes in Acute Appendicitis

Abstract: Background: Coronavirus disease 2019 has posed significant challenges to the provision of elective and emergency general surgical care. Patterns of presentation have changed and management pathways have also been adapted, moving to more non-operative management (NOM) for some conditions. We investigated how COVID-19 changed the volume of emergency general surgery operating in our district general hospital (DGH). We aimed to evaluate the impact of NOM on outcomes in acute appendicitis.Methods: A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Surgical societies put forth guidelines for management of AA, encouragin NOM for both uncomplicated and complicated appendicitis 30 . As previously discussed, this led to decreased operative management 1,23–25 . In comparison with pre-COVID studies suggesting suitable efficacy and safety of NOM of uncomplicated AA, 31 our study found significantly higher readmission, mortality, and LOS for both COVID-negative and COVID-active patients who underwent NOM.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Surgical societies put forth guidelines for management of AA, encouragin NOM for both uncomplicated and complicated appendicitis 30 . As previously discussed, this led to decreased operative management 1,23–25 . In comparison with pre-COVID studies suggesting suitable efficacy and safety of NOM of uncomplicated AA, 31 our study found significantly higher readmission, mortality, and LOS for both COVID-negative and COVID-active patients who underwent NOM.…”
Section: Discussionsupporting
confidence: 53%
“…30 As previously discussed, this led to decreased operative management. 1,[23][24][25] In comparison with pre-COVID studies suggesting suitable efficacy and safety of NOM of uncomplicated AA, 31 our study found significantly higher readmission, mortality, and LOS for both COVID-negative and COVID-active patients who underwent NOM. Among COVID-negative patients, both NOM and operative groups were relatively healthy at baseline, as demonstrated by low comorbidity index (CCI, <1).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation